Sequencing and bioinformatics analysis of exosome-derived miRNAs in mouse models of pancreatic injury induced by OSA - Lan, Jiuhuang; Lin, Jiayi; Guo, Yaopeng; Ji, Meilin; Lin, Yizhao; Chen, Qingshi (Frontiers in Physiology, 2025)
IntroductionThe role of exosomal miRNAs involved in the pathogenesis and development of pancreatic injury caused by obstructive sleep apnea (OSA) remains unclear. Here, miRNA sequencing (miRNA-seq) was used to investigate the expression profile of exosomal miRNAs in pancreatic tissue in a mouse model of chronic intermittent hypoxia (CIH) -induced pancreatic injury.MethodsFirstly, exosomes were isolated from pancreatic tissues of mice subjected to chronic intermittent hypoxia (CIH) or control conditions. Then, miRNA sequencing was performed, and differential expression analysis identified DE miRNAs. The potential functions of target genes were predicted by GO and KEGG analyses. Finally, a ceRNA interaction network was constructed to illustrate the relationships between miRNAs and targeted mRNAs.ResultsA total of 55 newly predicted miRNAs and 277 existing miRNAs were identified in pancreatic tissue exosomes from the mouse model of chronic intermittent hypoxic-induced pancreatic injury. 3 upregulated and 33 downregulated miRNAs with differential expression were identified. 8 exosome-derived miRNAs were selected to construct CNC networks to predict target genes. Some targets and pathways were elucidated by GO analysis and KEGG analysis.ConclusionOur work first comprehensively studied the expression profile of exosome-derived miRNA in pancreatic tissue of mouse models of OSA-induced pancreatic injury, bringing fresh perspectives on managing diabetes mellitus brought on by OSA.